1999
DOI: 10.1164/ajrccm.159.1.9804063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Grass Pollen Exposure on Exhaled Nitric Oxide in Asthmatic Children

Abstract: Exhaled nitiric oxide (NO) is increased in exhaled breath of asthmatic patients. The aim of this study was to investigate the longitudinal changes of exhaled NO outside and during the pollen season in pollen-allergic asthmatic children. Twenty-one children (age 6 to 16 yr), with a seasonal allergic asthma sensitive to grass pollen, underwent measurements of exhaled NO and pulmonary function before (March), during (May), and after (November) the pollen season. Exhaled NO was measured by a tidal breathing method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
66
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 26 publications
12
66
2
3
Order By: Relevance
“…Interestingly, a reduction in the average orally exhaled NO level was noted on the morning of day 7, which was a Monday. This may indicate a relationship between NO and stress or exposure to environmental factors like allergen or pollution [23,24]. The authors conclude that this reduction was not due to drift in the setup, since some subjects showed a decrease while others showed an increase between the days 3 and 7.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, a reduction in the average orally exhaled NO level was noted on the morning of day 7, which was a Monday. This may indicate a relationship between NO and stress or exposure to environmental factors like allergen or pollution [23,24]. The authors conclude that this reduction was not due to drift in the setup, since some subjects showed a decrease while others showed an increase between the days 3 and 7.…”
Section: Discussionmentioning
confidence: 92%
“…BARALDI et al [23] demonstrated that, during the pollen season, FE,NO increased significantly in spite of a lack of significant changes in FEV1, and also showed a relatively high FE,NO in these patients outside the grass pollen season, in agreement with the hypothesis that mild airway inflammation may persist even in the absence of symptoms [14]. A significant time-dependent modulation of FE,NO during house dust mite avoidance has previously been observed in a group of allergic asthmatic children during a stay in the Alpine environment, despite discontinuation of steroid therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…FE,NO has been demonstrated to be more promptly modified by exposure to or avoidance of relevant allergens in allergic asthmatic children [23,24] than lung function.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that sensitization to some allergens is more strongly related to exhaled NO than sensitization to others. 12,13 There is evidence that exposure to perennial allergens, such as house dust mite, are more likely to cause airway inflammation than exposure to seasonal allergens. An…”
mentioning
confidence: 99%
“…12 Also, cat dander is a perennial allergen and has been associated with asthma symptoms. Exhaled NO is also increased in atopic children and among symptomatic subjects.…”
mentioning
confidence: 99%